Avalanche Multiplication and Excess Noise in Thin Heterojunction AlxGa1_xAs/GaAs Avalanche Photodiodes - Low, Lay Chen (2010)
A general heterojunction avalanche photodiode (HAPD) model is developed to simulate avalanche characteristics in single heterojuntion avalanche photodiode.